Affective health and countermeasures in long-duration space exploration. Issue 5 (May 2022) - Gatti, Matteo; Palumbo, Rocco; Di Domenico, Alberto; Mammarella, Nicola
Abstract: Background: Space research is shifting attention toward interplanetary expeditions. Therefore, whether long-duration spaceflight may influence affective health is becoming an urgent issue. Method: To this end, we undertook a literature search and reviewed several behavioral simulation studies on Earth that focused on affective components in space. We concluded with studies showing how spaceflight can impact on affective health of astronauts with a positively laden trajectory. Results: By analyzing the multifaceted theoretical concept of affective health, we show that there is a variety of affective states (e.g., stress, coping, adaptation, and resilience) that can be differently affected by spaceflight. Conclusions: Countermeasures geared toward promoting positive emotions could play a key role in positive adaptation to extreme environments and thus during long-duration space missions may benefit. Subjective resilience plays a mediating role in adaptation, but its definition needs to be deepened in order to develop robust countermeasures that may prevent the onset of emotional disorders. Abstract : Emotion, Affective health, Resilience, Mood, Stress, Space mission.